EVALUATING THE GROUNDWATER QUALITY IN THE SATNA DISTRICT'S RAM NAGAR, RAGHURAJ NAGAR, AND RAMPUR BAGHELAN TAHSILS FOR BOTH DRINKING AND IRRIGATION PURPOSES IN MADHYA PRADESH - Kushwaha, Manish; Sikarwar, R.L.S. (ShodhKosh: Journal of Visual and Performing Arts, 2024)
This study also shows seasonal variations in the quality of the water and a little increase in a few chosen metrics when pre- and post-monsoon data were compared. It suggests that in the ensuing years, a few parameters might surpass the maximum amount of contamination. In present study underground water quality of some selected region at Satna district on the basis of selected parameters like PH, Temperature, Electrical Conductivity, Total hardness, TDS, BOD, NO3-, SO4-2, PO4-3, Cl-, F-, HCO3-, Mg++, K+, Alkalinity, E. coli and Alge. It was observed that underground water quality in selected area is not bad for drinking, domestic and agriculture purposes. Subsurface water quality in a few chosen regions of Satna district is currently being studied. Selected metrics, including temperature, electrical conductivity, total hardness, TDS, BOD, NO3-, SO4-2, PO4-3, Cl-, F-, HCO3-, Mg++, K+, alkalinity, E. coli, and algae, are taken into account. It was found that the subsurface water quality in a chosen location is suitable for residential use, drinking, and agricultural uses. This study also express seasonal variation of water quality and slight increment in some selected parameters were observed when data of pre mansoon and post mansoon compared. It indicates that some parameter may cross maximum contamination level in next upcoming years. This study also shows seasonal variations in the quality of the water and a little increase in a few chosen metrics when pre- and post-monsoon data were compared. It suggests that in the ensuing years, a few parameters might surpass the maximum amount of contamination.